ANALISIS LAHAN KRITIS DAN ARAHAN LAHAN DALAM PENGEMBANGAN WILAYAH PADA SUBDAS DI KABUPATEN KAYONG UTARA MENGGUNAKAN TEKNIK PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS - Murti Anom Suntoro; Dwi Astiani; Wiwik Ekyastuti (Universitas Tanjungpura, 2019)
Critical land is a damaged land, thus losing or decreasing its function to the specified or expected limits. The identification and critical lands mapping is essential for the planning and determination of priority watersheds in order to the utilization and development of natural resources and land rehabilitation and soil conservation. Remote sensing is a technique that enable people to collect data without direct field measurement. The using of Landsat 8 image then analyzed by using Geographic Information System (GIS) is being expected to improve the ability to classify land cover, the map was then overlad with parameter map based on Regulation of Director General of Management of Watershed and Social Forestry Number P. 4 / V-Set / 2013 about technical guidance on the preparation of spatial data of other critical lands to identify critical lands in Kayong Utara Regency.Keywords: Degraded land, Geographic Information System (GIS), Remote sensing, overlay